Guest satisfaction survey at the Aquaticum Debrecen Thermal and Wellness Hotel - Hevessy , Gábor; Vargáné Csobán, Katalin (Applied Studies in Agribusiness and Commerce, 2013)
Aquaticum Debrecen Thermal and Wellness Hotel is one of the most successful hotels in the North Great Plains region as well as in Hungary. The key to success lies in high level customer satisfaction. On the one hand only the satisfied guests will return to the hotel, on the other hand the guests’ positive or negative opinions will be shared with thousands of potential customers immediately by means of the Internet. Consequently, exploring the main factors of guest satisfaction has never been so important as nowadays. An online questionnaire system was introduced to the hotel in 2010, which resulted in an increased number of customer responses, thus it became possible to analyse the various aspects of customer satisfaction in a greater detail. In the present study the critical factors of guest satisfaction are analysed. We investigated the guests’ willingness to return to the hotel, and found that there is no significant difference between the guests’ gender, age, permanent place of residence and the fact if they travel alone or with a company and their willingness to return to the hotel, i.e. guest satisfaction. However, business travellers’ opinion significantly differs from the recreational travellers’ views concerning their return to the hotel. Business travellers are less satisfied and less willing to return. Furthermore, we investigated whether the problems experienced by the guests in the hotel influence the guests’ willingness to return to the hotel. We found that the guests who experienced problems are less willing to return. However, we also concluded that there was no significant difference in their willingness to return among those guests who experienced problems during their stay and these were efficiently handled, and those guests who did not experience any problem.